2016
DOI: 10.1111/jog.13137
|View full text |Cite
|
Sign up to set email alerts
|

Differential micro ribonucleic acid expression profiling in ovarian endometrioma with leuprolide acetate treatment

Abstract: To our knowledge, this is the first report profiling the miRNAs of endometrioma under leuprolide acetate treatment. The expression of seven miRNAs was modulated, concomitant with the disease state. This result gives new insight into the effects of leuprolide acetate treatment. Further investigation using quantitative reverse transcriptase-polymerase chain reaction and immunohistochemistry will allow us to validate the results of this study and to explore new therapeutic targets and biomarkers of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…All animals were housed in the SPF environment and got unlimited water and food. 5.0×10 6 Hep-2 cells were injected into the lift flank leg of each nude mouse. They were randomly divided into two groups with treatment of 1) shRNA-NC, and 2) TrkB-shRNA1.…”
Section: The Xenograft Tumor Model Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…All animals were housed in the SPF environment and got unlimited water and food. 5.0×10 6 Hep-2 cells were injected into the lift flank leg of each nude mouse. They were randomly divided into two groups with treatment of 1) shRNA-NC, and 2) TrkB-shRNA1.…”
Section: The Xenograft Tumor Model Assaymentioning
confidence: 99%
“…5 The differential expression of miRNAs may be related to the early onset and development of laryngeal carcinoma. 6 Interestingly, Several miRNAs have been reported to be associated with perturbation of the BDNF/TrkB pathway. 7 TrkB is a 145-kDa receptor tyrosine kinase which can be activated by brain-derived neurotrophic factor (BDNF) and neurotrophin 4 (NT4).…”
Section: Introductionmentioning
confidence: 99%
“…Serum levels of three miRNA biomarkers (miR-150, miR-451a, and miR-3613) reverted to normal levels in baboons that underwent treatment [121]. Kiba and colleagues identified five miRNAs (miR-146a, miR-142-3p, miR-136, miR-125b-1, and miR-15b) that were upregulated in ovarian endometrioma tissue following treatment with leuprolide acetate (a GnrH analog) [116]. Therapies with different mechanisms of action will likely impact a different set of miRNAs, several of which have been identified in cell culture experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Chang et al found that miR-125b directly binds to BMPR1B, a tumor suppressor of in ovarian cancer, and found single-nucleotide polymorphisms in this binding site that correlated with susceptibility to endometriosis [115]. Altered expression of miR-125b was also reported in ovarian endometriomas after leuprolide acetate (GnrH analog) treatment, suggesting its potential as a biomarker for monitoring treatment response [116].…”
Section: Mir-125bmentioning
confidence: 99%
“…Generally, clinicians provide the same treatment options for all types of endometriosis: hormonal suppression medications or surgical intervention, and thus there is no utility for signature testing specific to the type of lesion (ovarian, deep infiltrating, and peritoneal). Furthermore, is has been suggested that miRNA serum testing could be used as a biomarker to show response to hormonal therapy [11]. However clinically, response to therapy is determined by improvement of patients' subjective symptoms.…”
Section: Editorialmentioning
confidence: 99%